Homogeneous and Heterogeneous Photocatalysis for the Treatment of Pharmaceutical Industry Wastewaters: A Review - Maria Antonopoulou (Toxics, 2022)
Pharmaceuticals are biologically active compounds used for therapeutical purposes in humans and animals. Pharmaceuticals enter water bodies in various ways and are detected at concentrations of ng L−1–μg L−1. Their presence in the environment, and especially long-term pollution, can cause toxic effects on the aquatic ecosystems. The pharmaceutical industry is one of the main sources introducing these compounds in aquatic systems through the disposal of untreated or partially treated wastewaters produced during the different procedures in the manufacturing process. Pharmaceutical industry wastewaters contain numerous pharmaceutical compounds and other chemicals and are characterized by high levels of total dissolved solids (TDS), biochemical oxygen demand (BOD) and chemical oxygen demand (COD). The toxic and recalcitrant nature of this type of wastewater hinders conventional biological processes, leading to its ineffective treatment. Consequently, there is an urgent demand for the development and application of more efficient methods for the treatment of pharmaceutical industry wastewaters. In this context, advanced oxidation processes (AOPs) have emerged as promising technologies for the treatment of pharmaceutical industry wastewaters through contaminant removal, toxicity reduction as well as biodegradability improvement. Therefore, a comprehensive literature study was conducted to review the recent published works dealing with the application of heterogeneous and homogeneous photocatalysis for pharmaceutical industry wastewater treatment as well as the advances in the field. The efficiency of the studied AOPs to treat the wastewaters is assessed. Special attention is also devoted to the coupling of these processes with other conventional methods. Simultaneously with their efficiency, the cost estimation of individual and integrated processes is discussed. Finally, the advantages and limitations of the processes, as well as their perspectives, are addressed.